Por uma redução dos graus de separação entre Jeremy Bentham e John Rawls: aproximações entre o utilitarismo benthamiano e a justiça como equidade - Parenza, Fabrini Landevoigt (Universidade do Vale do Rio dos Sinos, 2021)
This work is about utilitarianism, proposed by Jeremy Bentham in the 18th century, justice as fairness, developed by John Rawls in the 20th century, with its unfavorable statements towards the widely understood utilitarianism, and possible parallels between both moral and political philosophy theories. The goal is to initiate and find, by consulting some of Jeremy Bentham's works, a definition of utilitarianism and of the rational consequentialist criterion of utility, proposed by moral and political philosophy, developed with rule utilitarianism, which is related with Law and legislation. Then, the research focuses on justice as fairness, proposed by John Rawls, aiming to understand it as an alternative and as a critic to the utilitarian doctrine. Finally, the relevance of the critics of common and of Rawls can be verified, applied to Bentham's utilitarianism as well as possible parallels between both theories, both in their destination to the legislator and in their moral justification. The dialectic study is supported by the bibliographic review of the main works of the philosophers whose theories are being analyzed, as well as by contemporary commentators, both national and foreign. Furthermore, we researched educational works for concepts and elements of moral and political philosophy
Keywords: Utilitarismo; Jeremy Bentham; Justiça como equidade; John Rawls; Utilitarianism; Justice as fairness